The Role of Packaging and Marketing in MSME Development in Mekarjaya Village, Arjasari District, Bandung Regency - Nurhalisa, Siti; Hartono, Kusdi; Syamsiah , Nur; Sayanti, Deuis (Jurnal Pengabdian Masyarakat, 2025)
Purpose: Micro, Small, and Medium Enterprises (MSMEs) in Mekarjaya Village face significant challenges in product packaging and marketing, resulting in limited market competitiveness. This research aims to increase MSME capacity through education, training, and mentoring in innovative packaging design and digital marketing strategies. Method: The study employed Participatory Action Research (PAR) methodology with qualitative data collection through surveys, observations, and interviews, involving active community participation throughout the research process in Mekarjaya Village, Bandung Regency. Practical Applications: The implemented activities including socialization, packaging training, labeling, and social media marketing resulted in significant improvements, with a 20% sales increase and expanded market reach for assisted MSMEs through enhanced product presentation and digital marketing approaches. Conclusion: This empowerment strategy demonstrates potential in improving MSME branding and competitiveness through digital media utilization. Ensuring sustainability and enabling replication in other regions requires institutional support, long-term evaluation, and contextual adjustments to local conditions.